Structural and functional characteristics of myocard in patients with different forms of atrial fibrillation - L. I. Vasilyeva; S. O. Pyvovarova; L. V. Sapozhnychenko; O. S. Kalashnykova; V. G. Dzyak (Zaporožskij Medicinskij Žurnal)
Aim. To study structural and functional characteristics of myocard in patients with different forms of atrial fibrillation. Atrial fibrillation is the most prevalent arrhythmia in clinical practice. Atrial fibrillation is a progressive disease: the duration of paroxysms increases over time and paroxysmal atrial fibrillation transforms to persistent, the last one becomes refractory to pharmacological and electrical cardioversion in time and transforms to permanent. So assessment of myocardial remodeling in patients with persistent and permanent atrial fibrillation is very actual.